The Role of Auditor Experience, Whistleblowing, and Red Flags on Auditor Fraud Detection - Tan, Willy; Kuntadi, Cris (Budapest International Research and Critics University, 2022)
Auditors have a big responsibility for fraud detection. Although auditors often find it difficult to detect fraud, the auditor has a big responsibility in detecting fraud in every audit assignment. The purpose of this study is to provide an understanding of the role of auditor experience, whistleblowing, and red flags on auditor fraud detection. The method used in this study uses the literature review method. The results of the study show that there is an effect of experience, whistleblowing, and red flags on auditor fraud detection. Suggestions from this study can be seen that there are many other variables that can effect on auditor fraud detection. In addition, in previous studies, it can be seen that there are several conflicting research results so that it becomes a challenge for further research to obtain the results of hypothesis testing.